Outsourcing peace. Private military and security companies. A setback to security sector reform in post conflict and transition states? - Mehboob, Cynthia (2017)
To what extent does the privatisation of security effect the ongoing Security Sector Reform (SSR) in post-conflict and transition States? Are Private Contractors capable of performing security sector reform operations at all? Using J.S. Mill’s method of agreement and disagreement coupled with process tracing techniques of investigation, this dissertation examines the extent to which Private Military and Security Companies effect the post conflict SSR operations in Afghanistan, Colombia and Iraq. Beginning with an inquiry into the nature and scope of PMSCs operations, the paper attempts to assess, if PMSCs are capable of performing post-conflict reconstruction of a states’ security architecture at all. The findings suggest that PMSCs are efficient actors and capable of demonstrating strength and speed when performing “train and equip” operations for the armies of failing states. However, PMSCs at present are incapable of taking a holistic approach towards SSR implementation and operations like ‘reform and development’ are beyond the scope of their abilities. Using, cost, legitimacy and effectiveness as indictors, the dissertation notes that the liberal discourse rubric which asserts that PMSCs are more cost effective, is a façade by the donor states to avoid political accountability. PMSCs operate in an accountability and oversight vacuum, where mismanagement of funds, frauds and corruption committed by PMSCs is rampant. This situation makes PMSCs, far more expensive than a national army. Hence, contracting more PMSCs in post conflict scenarios by donor states and organisations is a way of evading not economic but political costs. However, it cannot be ruled out that PMSCs can prove to be very valuable and effective contributors in contingency operations, if they are sent on the field after a careful overhaul of the existing ineffective legal regime under which they function.